INTERFERENSI GRAMATIKAL BAHASA INDONESIA DALAM PERCAKAPAN BERBAHASA ARAB SANTRI PTYQM KUDUS - Sholihah, Niswatush (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2019)
This study discusses the forms, causes and ways of overcoming Indonesian grammatical interference in Arabic conversations of the students of Pondok Tahfidz Yanbu'ul Qur'an Menawan (PTYQM) Kudus. This research is a qualitative research with a sociolinguistic approach. The method of providing data uses the listening and competent methods, and documentation. The method of data analysis uses the translational equivalent method where the determinant is another language, namely Indonesian. The results obtained are: Grammatical interference in the Arabic language in Arabic conversations in PTYQM Kudus, which consists of morphological and syntactic interference. Morphological interference that occurs in the form of affixation and reduplication processes. Whereas syntactic interference occurs at the level of phrases, clauses, and sentences. Interference at phrase level occurs at tarkīb ismy (nominal phrase), tarkīb fi'ly (verbal phrase), tarkīb ‘adady (number phrase), tarkīb żarfy (front phrase), and tarkīb nida’iy (vocational phrase). Interference at the clause level consists of adding elements and using Indonesian elements. Interference at sentence level consists of changes in sentence structure, use of Indonesian elements, omission of elements, addition of elements, and incorrect use of particles. Factors causing grammatical interference consist of structural factors and non-structural factors. Structural factors are the differences between the grammatical system between Indonesian and Arabic. While non-structural factors such as: bilingual speakers and speech partners, Indonesian language habits carried on the santri Arabic, inadequate Arabic vocabulary, learning styles by translating, fear of being sanctioned, and compulsory language regulatory factors that apply at PTYQM. Interference can be overcome by: instilling awareness about the interference that occurs, giving attention and emphasis in drill students to use the correct form of interference, accustom students to use the correct Arabic structure and rules, write the correct form of interference occur on boards posted in places frequented by students, train students to translate Indonesian into Arabic contextually, provide knowledge of Arabic culture that is different from Indonesian.